Acute in vitro and in vivo toxicity of a commercial grade boron nitride nanotube mixture. Issue 8 (14th September 2017) - Kodali, Vamsi K.; Roberts, Jenny R.; Shoeb, Mohammad; Wolfarth, Michael G.; Bishop, Lindsey; Eye, Tracy; Barger, Mark; Roach, Katherine A.; Friend, Sherri; Schwegler-Berry, Diane; Chen, Bean T.; Stefaniak, Aleksandr; et al.
Abstract: Boron nitride nanotubes (BNNTs) are an emerging engineered nanomaterial attracting significant attention due to superior electrical, chemical and thermal properties. Currently, the toxicity profile of this material is largely unknown. Commercial grade BNNTs are composed of a mixture (BNNT-M) of ∼50–60% BNNTs, and ∼40–50% impurities of boron and hexagonal boron nitride. We performed acute in vitro and in vivo studies with commercial grade BNNT-M, dispersed by sonication in vehicle, in comparison to the extensively studied multiwalled carbon nanotube-7 (MWCNT-7). THP-1 wild-type and NLRP3-deficient human monocytic cells were exposed to 0–100 µg/ml and C57BL/6 J male mice were treated with 40 µg of BNNT-M for in vitro and in vivo studies, respectively. In vitro, BNNT-M induced a dose-dependent increase in cytotoxicity and oxidative stress. This was confirmed in vivo following acute exposure increase in bronchoalveolar lavage levels of lactate dehydrogenase, pulmonary polymorphonuclear cell influx, loss in mitochondrial membrane potential and augmented levels of 4-hydroxynonenal. Uptake of this material caused lysosomal destabilization, pyroptosis and inflammasome activation, corroborated by an increase in cathepsin B, caspase 1, increased protein levels of IL-1β and IL-18 both in vitro and in vivo . Attenuation of these effects in NLRP3-deficient THP-1 cells confirmed NLRP3-dependent inflammasome activation by BNNT-M. BNNT-M induced a similar profile of inflammatory pulmonary protein production when compared to MWCNT-7. Functionally, pretreatment with BNNT-M caused suppression in bacterial uptake by THP-1 cells, an effect that was mirrored in challenged alveolar macrophages collected from exposed mice and attenuated with NLRP3 deficiency. Analysis of cytokines secreted by LPS-challenged alveolar macrophages collected after in vivo exposure to dispersions of BNNT-M showed a differential macrophage response. The observed results demonstrated acute inflammation and toxicity in vitro and in vivo following exposure to sonicated BNNT-M was in part due to NLRP3 inflammasome activation.